The Relationship between the Quality of Service of Donor Blood Collection Officers to the Level of Donor Satisfaction at UDD PMI Yogyakarta City - Betty Prasetyaswati; Christina Roosarjani; Dita Yustina Nopianti (Nur Science Institute, 2023)
Quality system is key to ensuring availability of blood stock. In addition to the availability of blood stock is influenced by quality, donor satisfaction can also affect the availability of blood stock. This research is a descriptive research with survey method. The study population was donors in the UDD PMI building in Yogyakarta City. The sampling technique is random sampling of 95 respondents. Data collection using closed and open- ended questionnaires. Data analysis techniques use univariate and bivariate analysis. Results: From the univariate test, the service of officers was in the quality category (100%) while donor satisfaction was in the satisfied category (100%). Regression data analysis with a calculation result of 52.9%, which means that there is an influence on the Donor Blood Draw Officer Service Quality variable on the Donor Satisfaction variable and the remaining 47.1% is influenced by other factors. The significance value of 0.000<0.05 is significant and the coefficient value of 0.574** means that the value shows a positive number, so that the direction of the relationship between variables is unidirectional.